Avaliação da influência da adição de grafeno na resina epóxi aplicada à reforços estruturais com fibra de carbono em vigas de concreto armado - Abrahão, Taila Brandes (2025)
Structural strengthening plays a fundamental role in the preservation and retrofitting of structures that are nearing the end of their service life, were built according to outdated standards, or require adaptation to new uses that exceed their original capacity. Among the various available techniques, the use of carbon fiber reinforced polymers (CFRP) stands out due to their mechanical strength, corrosion resistance, low density, and minimal alteration of the geometry of the strengthened element. However, premature debonding of CFRP, often caused by adhesive characteristics such as brittle failure mode and low fracture toughness, can compromise the structural stability of the system. In this context, recent research has focused on enhancing the properties of polymer matrices through the incorporation of nanomaterials such as graphene, which provides increased toughness and mechanical strength to the composite. Nevertheless, proper dispersion is essential for the effective performance of the reinforcement, requiring the use of techniques such as ultrasonication or shear mixing to ensure homogeneity. With this in mind, the objective of this study was to evaluate the influence of graphene addition to epoxy resin used in CFRP structural strengthening of reinforced concrete beams. The study was divided into four parts: material characterization, investigation of graphene dispersion in the resin, analysis of the composite produced using the best dispersion method, and application of this composite as an adhesive for CFRP strengthening of reinforced concrete beams. Three different dispersion techniques were employed: ultrasonic bath, ultrasonic processors, and torque rheometer (shear mixing). The materials and compositions were characterized using Fourier transform infrared spectroscopy (FTIR), thermogravimetric and differential thermal analysis (TGA/DTA), differential scanning calorimetry (DSC), X-ray diffraction (XRD), atomic force microscopy (AFM), Raman spectroscopy, optical microscopy (OM), transmission electron microscopy (TEM), and tensile strength testing. Based on the results, shear mixing was selected as the most effective method for composite production and subsequent application in CFRP strengthening. The composite was evaluated using FTIR, TGA/DTA, DSC, and tensile strength tests. The beams were tested under four-point bending to determine the cracking and ultimate stresses, as well as to evaluate the failure modes of the specimens. The experimental data showed that the torque rheometer provided the most effective graphene dispersion, resulting in the composite with the most homogeneous distribution and the best balance between strength and elastic modulus. When applied as an adhesive in CFRP strengthening, no statistical difference was observed in cracking and ultimate stresses compared to the neat resin. This performance is associated with the failure mode and factors such as dispersion quality, interaction with concrete, and stiffness of the reinforcement.